Integration of Tabe’ Culture in Character Education of Elementary School Students: Systematic Literature Review within the Context of the Merdeka Curriculum - Ahmar Ahmar; Eko Handoyo; Hanafi Hussin; Indriana Eko Armadi (Amorti: Jurnal Studi Islam Interdisipliner, 2026)
Character education is a key focus in the implementation of the Merdeka Curriculum, particularly at the elementary school level. However, the rise of globalization and digital culture has led to a decline in students’ values of courtesy, respect, and social ethics. One approach that can be taken is to integrate local wisdom into the educational process. The Tabe’ culture, as a cultural tradition of the Bugis-Makassar people, embodies values of respect, politeness, empathy, and social responsibility that are relevant to strengthening students’ character. This study aims to analyze the implementation of Tabe’ culture in elementary school students’ character education through a Systematic Literature Review (SLR) approach. The study followed the PRISMA guidelines by reviewing national articles published between 2019 and 2025 via Google Scholar, GARUDA, and accredited national journals. Of the 63 articles identified, 20 met the inclusion criteria and were analyzed using thematic analysis. The results indicate that the implementation of Tabe’ culture occurs through daily routines, teacher modeling, integration into learning, and the development of school culture. The character values fostered include respect, courtesy, discipline, empathy, and social responsibility. This study also found that the Tabe’ culture has strong relevance to the strengthening of the Pancasila Student Profile within the Merdeka Curriculum. The research findings affirm that local culture can serve as a contextual strategy for strengthening character education in elementary schools.